2017
DOI: 10.1007/s10151-017-1645-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and persistence of cryptoglandular anal fistula: a systematic review

Abstract: Anal fistulas continue to be a problem for patients and surgeons alike despite scientific advances. While patient and anatomical characteristics are important to surgeons who are evaluating patients with anal fistulas, their development and persistence likely involves a multifaceted interaction of histological, microbiological, and molecular factors. Histological studies have shown that anal fistulas are variably epithelialized and are surrounded by dense collagen tissue with pockets of inflammatory cells. Yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 65 publications
1
71
0
10
Order By: Relevance
“…Clinically, about 60% of perianal abscess cases progress to anal fistula, which requires more complicated surgery. The development of anal fistula is attributed to the primary infection resulted from the entry of rectal contents into anal sinus, which if not promptly controlled, would lead to chronic inflammation and recurrent infection, leading to the formation of fibrotic canal wall in abscess cavity and in turn inadequate drainage . Along with these findings, by showing the association of IL‐17 with anal fistula formation, the present study implicated the potential involvement of IL‐17 in the pathophysiology of anal fistula.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Clinically, about 60% of perianal abscess cases progress to anal fistula, which requires more complicated surgery. The development of anal fistula is attributed to the primary infection resulted from the entry of rectal contents into anal sinus, which if not promptly controlled, would lead to chronic inflammation and recurrent infection, leading to the formation of fibrotic canal wall in abscess cavity and in turn inadequate drainage . Along with these findings, by showing the association of IL‐17 with anal fistula formation, the present study implicated the potential involvement of IL‐17 in the pathophysiology of anal fistula.…”
Section: Discussionsupporting
confidence: 67%
“…Perianal abscess can be treated straightforwardly by surgical incision and draining. Clinically, 40–60% of perianal abscess cases will develop to anal fistula, of which the management can be more complicated . The molecular pathogenesis underlying the progression from perianal abscess to anal fistula has remained to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…2c), which might be caused by reactive hyperplasia of tissues surrounding the stula tract under stimulation from the thread. 4. ASC-microcarrier 6 transplantation for anal stula mainly promotes tissue regeneration through multi-directional differentiation, and it has been found that PI3K/AKT signaling pathway molecules are signi cantly enriched…”
Section: Pathological Examinationmentioning
confidence: 99%
“…Adipose-derived stem cells (ASCs) are mesenchymal stem cells that are found in adipose tissues. They possess self-regeneration and multi-differential potential and belong to the class of adult stem cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…Patient predisposition may explain the latter observation, as it has been shown that there is an increased expression of pro-inflammatory cytokines and epithelial-to-mesenchymal cell transition in CPF. Therefore, molecular mechanisms may also interfere in pathogenesis and also persistence of CPF [47].…”
Section: Fistulotomy For the Low Cpfmentioning
confidence: 99%